SIFAT FISIK DAN MEKANIK PAPAN SEMEN DARI LIMBAH PENGGERGAJIAN BERDASARKAN UKURAN PARTIKEL DAN KOMPOSISI SEMEN - Syaifudin, Muhammad Aprizal; Dirhamsyah, M; Wardenaar, Evy (Universitas Tanjungpura, 2020)
This study aims to examine the physical and mechanical properties of cement boards from sawing waste based on raw material composition and particle size, as wellÂ to get the best sawing waste particle size and raw material composition according to JIS A5417-1992 standard. The research was carried out at the Wood Workshop Laboratory, Wood Technology Laboratory, Wood Processing Laboratory and PT Duta Pertiwi Nusantara Pontianak. This study uses a completely randomized factorial design (CRD) with two factors, namely factor A (Particle Size) and factor B (composition of cement). The results showed the average value of density ranged from 0.6878 to 0.8094 gr / cm3, moisture content value ranged from 6.7057 to 10.0246%, thickess swelling value ranged from 0.3996 to 0.8773%, water absorption value ranged from 27.8949 - 49.0375%, MOE ranged from 412.6563-1411.7847 kg / cm2 and MOR value ranged from 2.1529-4.5909 kg / cm2. The particle size that affects the physical properties is the value of water absorption, while the composition of the material that affects the physical properties is the density, water content, thickness development and water absorption capacity. The particle size and composition of the material which influence the mechanical properties, namely the value of the flexural firmness and fracture firmness. Based on the results of cement board testing with particle composition and cement (1:2) with particle size passing 10 mesh restrained 20 mesh yields the best physical properties of cement board that meet the standards of JIS A 5417: 1992, while none of the cement boards MOE and MOR meet the testing standards mechanical properties according to JIS A 5417: 1992.Keywords: Cement board, composition of cement, particle size, sawing waste